A systematic review of economic evaluations of population-based sodium reduction interventions. - Silvia F Hope; Jacqui Webster; Kathy Trieu; Arti Pillay; Merina Ieremia; Colin Bell; Wendy Snowdon; Bruce Neal; Marj Moodie (PLoS ONE, 2017)
Objective To summarise evidence describing the cost-effectiveness of population-based interventions targeting sodium reduction. Methods A systematic search of published and grey literature databases and websites was conducted using specified key words. Characteristics of identified economic evaluations were recorded, and included studies were appraised for reporting quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Results Twenty studies met the study inclusion criteria and received a full paper review. Fourteen studies were identified as full economic evaluations in that they included both costs and benefits associated with an intervention measured against a comparator. Most studies were modelling exercises based on scenarios for achieving salt reduction and assumed effects on health outcomes. All 14 studies concluded that their specified intervention(s) targeting reductions in population sodium consumption were cost-effective, and in the majority of cases, were cost saving. Just over half the studies (8/14) were assessed as being of 'excellent' reporting quality, five studies fell into the 'very good' quality category and one into the 'good' category. All of the identified evaluations were based on modelling, whereby inputs for all the key parameters including the effect size were either drawn from published datasets, existing literature or based on expert advice. Conclusion Despite a clear increase in evaluations of salt reduction programs in recent years, this review identified relatively few economic evaluations of population salt reduction interventions. None of the studies were based on actual implementation of intervention(s) and the associated collection of new empirical data. The studies universally showed that population-based salt reduction strategies are likely to be cost effective or cost saving. However, given the reliance on modelling, there is a need for the effectiveness of new interventions to be evaluated in the field using strong study designs and parallel economic evaluations.